Trends in Contraceptive Practice; An Overview of Family Planning Clinic, Fatima Jinnah Medical University Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective: Contraceptive practices at Sir Ganga Ram Hospital, Lahore during last five years. Design: A Cross Sectional Study. Settings: Conducted in Family Planning Centre at Sir Ganga Ram Hospital, Lahore. Duration of study: From July, 2011 to June, 2015. Material & Method: The data regarding different methods of contraception utilized by married women aged 15-49 in Family Planning Centre at Sir Ganga Ram Hospital, Lahore was assessed. Result: Over five years, 6,763 contraceptive surgical procedures (Minilap) were performed. In 2496 females injectable contraceptives were used. 2383 intrauterine contraceptive devices were inserted. 5578 packets of oral contraceptive pills, 56411 packets of condoms were utilized. Implanons were inserted in 170 women. There is marked increased in women who relied on implanon. Conclusion: This study showed that there is rising trend in the use of implanon during 5 years in Family Planning Centre at Sir Ganga Ram Hospital, Lahore because Implanon is highly effective, easy to use and has minimum side effects. Implanon is not user dependent as compare to combined oral contraceptive pills and condoms.
Keywords: IUCDs (Intrauterine Contraceptive Devices), OCPs (Oral Contraceptives), CPR (Contraceptive Prevalence Rate)